A case of invasive pulmonary aspergillosis diagnosed by transbronchial lung biopsy during treatment for diabetic ketoacidosis in a type 1 diabetic patient. Issue 2 (February 2020) - Watanabe, Naoaki; Saito, Keisuke; Kiritani, Ayu; Fujimoto, Shota; Yamanaka, Yumie; Fujisaki, Ikumi; Hosoda, Chiaki; Miyagawa, Hanae; Seki, Yoshitaka; Kinoshita, Akira; Takeda, Hiroshi; Endo, Yasuhiko; et al.
Abstract: Invasive pulmonary aspergillosis (IPA) patients with non-hematological malignancy are far less than with hematological malignancy patients. We encountered a very rare case of IPA in which type 1 diabetes was the only conceivable risk factor. Further, according to the diagnostic categories of the European Organization for Research and Treatment of Cancer/Invasive Fungal Infections Cooperative Group and the National Institute of Allergy and Infectious Diseases Mycoses Study Group (EORTC/MSG) criteria for IPA, the frequency of proven diagnosis is very low. Here we report a proven IPA, which rapidly developed when the patient with type 1 diabetes was being treated for diabetic ketoacidosis, which was successfully treated with the combination therapy of voriconazole (VRCZ) and micafungin (MCFG), based on early diagnosis using bronchoscopy.